The security culture playbook - Carpenter, Perry (Wiley, 2022)
Mitigate human risk and bake security into your organization's culture from top to bottom with insights from leading experts in security awareness, behavior, and culture. The topic of security culture is mysterious and confusing to most leaders. But it doesn't have to be. In The Security Culture Playbook, Perry Carpenter and Kai Roer, two veteran cybersecurity strategists deliver experience-driven, actionable insights into how to transform your organization's security culture and reduce human risk at every level. This book exposes the gaps between how organizations have traditionally approached human risk and it provides security and business executives with the necessary information and tools needed to understand, measure, and improve facets of security culture across the organization. The book offers: An expose of what security culture really is and how it can be measured A careful exploration of the 7 dimensions that comprise security culture Practical tools for managing your security culture program, such as the Security Culture Framework and the Security Culture Maturity Model Insights into building support within the executive team and Board of Directors for your culture management program Also including several revealing interviews from security culture thought leaders in a variety of industries, The Security Culture Playbook is an essential resource for cybersecurity professionals, risk and compliance managers, executives, board members, and other business leaders seeking to proactively manage and reduce risk.